Further insights into the pathogenic mechanisms of haemotropic Mycoplasma ovis - Thlama, Bura Paul; Mohd Lila, Mohd Azmi; Che' Amat, Azlan; Chung, Eric Lim Teik; Kamaludeen, Juriah; Abdullah, Faez Firdaus Jesse (Penerbit Universiti Sains Malaysia,Universiti Sains Malaysia Press, 2024)
In this study, we examined the effects of experimental intraperitoneal infection with haemotropic Mycoplasma ovis (0.5ml of blood containing 80% parasitaemia) on selected serum biomarkers and cellular pathology in mice. After infection, M. ovis cells appeared in the blood films within one week. A dose-dependent peak of parasitemia was observed during the 3rd-week post-infection (pi), with a significant decrease in mean PCV between treatment versus control group at week 3 (t14 = -3.693, P < 0.02), week 5 (t14 = -2.096, P = 0.055), and week 7 (t14 = - 4.329, P = 0.001). There was a significantly (t8 = - 2.330, P = 0.048) lower serum oestrogen in treatment (10.38 ± 5.07) than control (17.43 ± 4.48), while serum progesterone was significantly (t8 = 5.415, P = 0.001) increased in treatment (27.37 ± 2.17) than control (15.92 ± 4.20). Serum haptoglobin was significantly (t8 = 8.525, P < 0.01) lower in treatment (8.72 ± 1.49) than control (18.16 ± 1.98) while the SAA was significantly (t8 = 3.362, P = 0.01) higher in treatment (16.79 ± 2.71) than control (11.59 ± 2.15). Prominent lesions observed in the ovary include degeneration, necrosis, vacuolation, and hypertrophy of the lutein cells in corpora lutea. In the lymph nodes, diffused cellular hyperplasia of the lymphoid tissue in the cortex. In the liver, degeneration and necrosis accompanied by leucocytic cellular infiltration and Kupffer cell proliferation within the sinusoids. There were diffused leucocytic infiltrations and proliferative lesions in the glomerulus of the kidneys. The disturbance in progesterone and ovarian pathology recorded here is a novel aspect of this study that highlights the potential role of haemotropic M. ovis in reproductive disorders. The observed changes in biomarkers and cellular reactions following M. ovis infection in the mouse may be further advanced in sheep and goats.